2013
DOI: 10.1123/jsr.22.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Lower Extremity Muscle Function After Anterior Cruciate Ligament Reconstruction

Abstract: Declines in quadriceps and soleus volitional muscle function were of lower magnitude in ACL-R subjects than in healthy matched controls. This response suggests an adaptation experienced by patients with quadriceps AMI that may act to maintain lower extremity function during prolonged exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 47 publications
3
32
0
Order By: Relevance
“…32 For the effect of ACLR on quadriceps CAR, the Cohen d effect size was 1.2; therefore, a minimum of 20 participants per group was needed 32 to find differences while maintaining a statistical power of 80% and an a level of .05.…”
Section: Lsi ¼ Aclr Limb Uninvolved Limb ð2þmentioning
confidence: 99%
“…32 For the effect of ACLR on quadriceps CAR, the Cohen d effect size was 1.2; therefore, a minimum of 20 participants per group was needed 32 to find differences while maintaining a statistical power of 80% and an a level of .05.…”
Section: Lsi ¼ Aclr Limb Uninvolved Limb ð2þmentioning
confidence: 99%
“…1 A history of ACL-R is also associated with a greater risk for chronic degeneration of the articular tissues of the knee, which leads to early-onset osteoarthritis. 2,3 Posttraumatic changes in quadriceps motor function may be associated with long-term disability in patients who have had ACL-R. 4,5 A wealth of evidence has suggested that ACL-R causes both immediate and long-term changes in quadriceps motor function, which can manifest as weakness, 6,7 inhibition, 6,8 and diminished power 9,10 and motor control. 11,12 Impaired quadriceps motor function is concerning to clinicians and scientists due to the primary role the quadriceps play in lower extremity locomotion, force attenuation, and functional stability about the knee.…”
mentioning
confidence: 99%
“…103,132 After ACLR, individuals also experience alterations in walking gait compared to healthy individuals years after surgery, including reductions in peak knee flexion angle, knee flexion moment, and knee extension moment during stance phase. 60,199,202 121,195 Therefore, it is imperative that return to sport assessments for this population include functional assessments during exercise when risk of second injury is greatest and neuromuscular control is compromised.…”
Section: Discussionmentioning
confidence: 99%
“…73,106,107,144 Patients with ACLR experience a significant decline in quadriceps strength compared to both the contralateral limb and healthy matched limb, 144,190 leading to asymmetric quadriceps strength. 91,174,208 These strength deficits in the involved limb may be from atrophied quadriceps 105 after surgical intervention causing a shift towards fatigue-resistant quadriceps 103,132,183 or may be changes in quadriceps activation. 73,144 Quadriceps activation failure is common bilaterally years after ACLR 73 even when quadriceps atrophy is no longer present.…”
Section: 137mentioning
confidence: 99%
See 1 more Smart Citation